Antifibrinolytics Reduce Blood Loss in Adult Spinal Deformity Surgery: A Prospective, Randomized Controlled Trial. Issue 8 (15th April 2015) - Peters, Austin; Verma, Kushagra; Slobodyanyuk, Kseniya; Cheriyan, Thomas; Hoelscher, Christian; Schwab, Frank; Lonner, Baron; Huncke, Tessa; Lafage, Virginie; Errico, Thomas
Abstract : Study Design: This is a prospective, randomized, double-blinded comparison of tranexamic acid (TXA), epsilon aminocaproic acid (EACA), and placebo used intraoperatively in patients with adult spinal deformity. Objective: The purpose of this study was to provide high-quality evidence regarding the comparative efficacies of TXA, EACA, and placebo in reducing blood loss and transfusion requirements in patients undergoing posterior spinal fusion surgery. Summary of Background Data: Spine deformity surgery usually involves substantial blood loss. The antifibrinolytics TXA and EACA have been shown to improve hemostasis in large blood loss surgical procedures. Methods: Fifty-one patients undergoing posterior spinal fusion of at least 5 levels for correction of adult spinal deformity were randomized to 1 of 3 treatment groups. Primary outcome measures included intraoperative estimated blood loss, total loss, (estimated blood loss + postoperative blood loss), and transfusion rates. Results: Patients received TXA (n = 19), EACA (n = 19), or placebo (n = 13) in the operating room (mean ages: 60, 47, and 43 yr, respectively); TXA patients were significantly older and had larger estimated blood volumes than both other groups. Total losses were significantly reduced for EACA versus control, and there was a demonstrable but nonsignificant trend toward reduced intraoperative blood loss in both antifibrinolytic arms versus control. EACA had significant reductions in postoperative blood transfusions versus TXA. Conclusion: The findings in this study support the use of antifibrinolytics to reduce blood loss in posterior adult spinal deformity surgery. Level of Evidence: 1 Abstract : This was a randomized, controlled, double-blinded comparison of tranexamic acid (TXA), aminocaproic acid, and control. Fifty-one adult patients were enrolled. Overall, aminocaproic acid demonstrated significant reduction in perioperative blood loss compared with control, and postoperative transfusion compared with TXA. TXA had a trend toward reduced blood loss compared with control.